Ultrazvočna diagnostika hemangiomov - Ključevšek, Damjana (Slovenska pediatrija, 2010)
Hemangiomas are the most common benign tumours of infancy. Girls are affected 3 - 5 times as often as boys. 60 % of hemangiomas are located in the cervicofacial region. Hemangiomas have a typical natural three-phase course, with proliferative, stable and involutive phases. Hemangiomas can be diagnosedon cIinical grounds in over 90 % of cases. Diagnostic imaging may be useful in cases of deep hemangiomas with normal overlying skin, cIinically atypical soft-tissue masses, for evaluation of the extension of obvious hemangiomas, cases of alarming hemangiomas, when immediate intervention is necessary, and for following the effectiveness of therapy. The basic imaging is ultrasound (US). Gray-scale US imaging ofhemangiomas is non-specific, hencethis should be supplemented by colour and power Doppler to assess vessel density (the number of colour flow signals/cm2) and by pulse Doppler to assessthe type ofvessels, the spectra offlow in the vessels with different Doppler parameters, and to define the possible presence of signs of arteriovenous communications. US can be very helpful in the differential diagnosis between hemangiomas and vascular malformations (particularly arteriovenous and venous) and from other non-vascular tumours in infancy. USguided biopsy may be necessary in uncIear and atypical cases.
Keywords: diagnostika; hemangiom; kožne novotvorbe; ultrazvočna diagnostika